Організаційний механізм підготовки національних проектів - Ніколаєв, В. П.; Шут, С. О. (Ways to Improve Construction Efficiency, 2014)
The article deals with the procedures and regulations of obtaining the status of national projects, determine their constituents, companies, managers, preparation and financing of pre-feasibility studies. The benefits of national projects versus traditional practice of capital investment as well as disadvantages compared with the standard procedures of projects planning are analyzed. The measures to improve the institutional mechanism of national projects are proposed.